Answer:
[tex]v_{0}=319.2 m/s[/tex]
Explanation:
We need to use the momentum and energy conservation.
[tex]p_{0}}=p_{f}[/tex]
[tex]mv_{0}=(m+M)V_{1}[/tex]
Where:
Conservation of energy.
We have kinetic energy at first and kinetic and potential energy at the end.
[tex](1/2)(m+M)V_{1}^{2}=(1/2)(m+M)V_{2}^{2}+(m+M)gh[/tex]
Here:
We can find V(2) using the definition of force at this point:
[tex]\Sigma F=(m+M)a_{c}=(m+M)(V_{2}^{2}/R)[/tex]
[tex]T-(m+M)gcos(\theta)=(m+M)a_{c}=(m+M)(V_{2}^{2}/R)[/tex]
[tex]cos(\theta) =(L-h)/L=(1.72-0.8)/1.72 [/tex]
[tex]\theta =57.66 [/tex]
Now, we can solve the equation to find V(2)
[tex]V_{2}=\sqrt{\frac{R*(T-(m+M)*g*cos(\theta))}{(m+M)}}[/tex]
[tex]V_{2}=\sqrt{\frac{1.72*(4.86-(0.01+0.75)*9.81*cos(57.66))}{(0.01+0.75)}}[/tex]
[tex]V_{2}=1.40 m/s[/tex]
Now we can find V(1) using the conservation of energy equation
[tex](1/2)V_{1}^{2}=(1/2)V_{2}^{2}+gh[/tex]
[tex]V_{1}=\sqrt{V_{2}^{2}+2gh}[/tex]
[tex]V_{1}=\sqrt{1.40^{2}+2*9.81*0.8}[/tex]
[tex]V_{1}=4.20 m/s[/tex]
Finally, using the momentum equation we find v(0)
[tex]v_{0}=\frac{(m+M)V_{1}}{m}[/tex]
[tex]v_{0}=\frac{(0.01+0.75)*4.20}{0.01}[/tex]
[tex]v_{0}=319.2 m/s[/tex]
I hope it helps you!